2019
DOI: 10.1002/fsn3.1244
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the flavor compounds in the cocoa powder production process

Abstract: Flavor is one of the most important quality properties of cacao beans, playing a key role in the admissibility of cocoa products, such as cocoa powder. This study examined the industrial processes influencing the flavor of cacao beans. The Ivory Coast cacao beans were used after their alkaline treatment with potassium carbonate (up to pH 7.5–8) and being roasted at 115–120°C for 60–70 min. The volatile components were extracted using Likens–Nickerson simultaneous distillation–extraction (SDE) apparatus. The vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 31 publications
1
28
0
Order By: Relevance
“…Cocoa, a significant agricultural commodity and a cash product of great economic importance in the world, is utilized as the crucial raw material for chocolate and cocoa powder manufacturing [ 1 ]. Specifically, the term ‘cacao’ indicates the raw cacao beans or trees, while the term ‘cocoa’ denotes the processed product cocoa or chocolates, however, the two terms have been used interchangeably in many countries, in particular Brazil and Spain [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cocoa, a significant agricultural commodity and a cash product of great economic importance in the world, is utilized as the crucial raw material for chocolate and cocoa powder manufacturing [ 1 ]. Specifically, the term ‘cacao’ indicates the raw cacao beans or trees, while the term ‘cocoa’ denotes the processed product cocoa or chocolates, however, the two terms have been used interchangeably in many countries, in particular Brazil and Spain [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cocoa, a significant agricultural commodity and a cash product of great economic importance in the world, is utilized as the crucial raw material for chocolate and cocoa powder manufacturing [ 1 ]. Specifically, the term ‘cacao’ indicates the raw cacao beans or trees, while the term ‘cocoa’ denotes the processed product cocoa or chocolates, however, the two terms have been used interchangeably in many countries, in particular Brazil and Spain [ 1 ]. The genus Theobroma contains 22 species classified into six sections, most native to the upper Amazon region in South America [ 2 ], whereas only T. cacao L. and T. grandiflorum (cupuassu) are explored commercially on a large scale.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors demonstrated that aroma and protein (as per matrix-assisted laser desorption/ionization time of flight [MALDI-TOF] MS) profiling could be used as a crop genetic improvement parameter. Alasti and coworkers [ 305 ] performed extensive research that focused on the effect of processing in cocoa powder production (i.e., n = 5 steps were monitored for volatile compound content: Raw ingredients, alkalinization, roasting, milling, pressing, and the product). Among the compounds identified, 2,3,5,6-tetramethylpyrazine increased almost tenfold from the cocoa beans to the powder.…”
Section: Selected Instrumental Techniques and Their Applicationsmentioning
confidence: 99%
“…As flavor traits may be influenced by volatile chemistry, there were data taken and analyzed from four time points to evaluate the samples: 0-h, 8-h, 16-h, and 24-h. Data were evaluated to determine if trends of metabolite classes could distinguish the profiles of the chocolate masses at each time point, specifically, for lipids (to include fatty acid ester formation), Maillard reaction products (MRPs), organic acids (and their esters, which are known to be formed during thermal processing of chocolate 34 ), aldehydes, ketones, and terpenes. Metabolite abundances were shown as a Log 2 Fold Change to express the data as a profile within a sample.…”
Section: Trends Among Chemical Classesmentioning
confidence: 99%